Impact of conditional cash transfers on enrolment in community-based health insurance among female-headed households in south Gondar zone, Amhara region, Ethiopia - Essa Chanie Mussa; Dessie Agegnehu; Emmanuel Nshakira-Rukundo (Elsevier, 2022)
Ethiopia has been implementing its flagship social protection programme, Productive Safety Net Programme (PSNP), since 2005, mainly in drought prone and chronically food insecure woredas. In 2011, the country also launched Community-Based Health Insurance (CBHI). However, the two large-scale social protection programmes are not integrated well. This study examines the impact of participation in the conditional cash transfer (CCT) component of the PSNP (Public Works or PW) on enrolment in the CBHI among female-headed households in Amhara region.Data for the study generated through a cross-sectional survey collected from 365 PW-participating and non-participating female-headed households in south Gondar zone, Ebinat woreda (district). Inverse-probability-weighted regression adjustment (IPWRA) estimator is used to evaluate the impact of participating in PW component on CBHI enrolment decisions.Enrolment in CBHI among female-headed households is 63.6%. Data also show that 61.2% of insured and 27.1% of non-insured households receive CCTs. The study finds that participating in PSNP's CCT component increases the probability of CBHI enrolment among female-headed households by 16.3 percentage points. The finding informs efforts in integrating social protection programmes among most vulnerable households in rural Ethiopia. It also gives useful insights on the role of PSNP's CCT component to achieving universal health coverage through increasing insurance enrolment among most vulnerable households in Ethiopia.